2005
DOI: 10.1187/cbe.05-08-0113
|View full text |Cite
|
Sign up to set email alerts
|

Infusing Active Learning into the Large-enrollment Biology Class: Seven Strategies, from the Simple to Complex

Abstract: The greatest single challenge to SMET pedagogical reform remains the problem of whether and how large classes can be infused with more active and interactive learning methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
155
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(175 citation statements)
references
References 25 publications
2
155
0
5
Order By: Relevance
“…We estimate that up to 120 students could be managed by the technique described in this report. In classrooms with > 120 students, the process may break down because the time needed for group reports would create too much idle time for the majority of students [14]. Guiding questions are needed to ensure that students identify learning issues [15].…”
Section: 06mentioning
confidence: 99%
“…We estimate that up to 120 students could be managed by the technique described in this report. In classrooms with > 120 students, the process may break down because the time needed for group reports would create too much idle time for the majority of students [14]. Guiding questions are needed to ensure that students identify learning issues [15].…”
Section: 06mentioning
confidence: 99%
“…The sessions using the SIDRA anonymous mode were designed according to recommendations for using ARS [31]. Preparing the MCQs was an extremely time consuming task [32], since we attempted to ensure that each question had an explicit pedagogical purpose [33]. The primary objective of the first part was to measure the increase/decrease in the participants' knowledge when using neural network-based audience response technology.…”
Section: Methodsmentioning
confidence: 99%
“…Preparing the MCQs and appropriate feedback text for each of the group of students' possible responses was an extremely time consuming task [32], since we attempted to ensure that each question had an explicit pedagogical purpose [33]. When writing feedback, academics confront a difficult task since the feedback should not be over-detailed so as to avoid confusing the students and to ensure that they can easily interpret it and get the point [61].…”
Section: Limitationsmentioning
confidence: 99%
“…15,54 It is the construction of applicable and effective questions that can be time consuming and often challenging. 9,55 It has been suggested that some of the most effective questions allow recently acquired knowledge to be used, focus on reasoning and aim to identify any student misconceptions. 9,56 As aforementioned, a benefit of LAP is that it allows the lecturer to adjust his or her teaching session based on learning needs identified by the students' responses.…”
Section: Negatives Of Lap For the Lecturermentioning
confidence: 99%